Reconciling Immigration and Agricultural Labor Concerns for a Sustainable State Economy - Chandra Bowden; Alexa Lamm; Hannah Carter; Tracy Irani; Sebastian Galindo (EDIS, 2013)
Immigration in Florida is a contested issue and having an understanding of this issue can help facilitate communication. This 6-page fact sheet provide brief but clear information about the trends in policies that can be used by Extension agents to increase educated conversations around immigration issues. Written by Chandra Bowden, Alexa Lamm, Hannah Carter, Tracy Irani, and Sebastian Galindo, and published by the UF Department of Agricultural Education and Communication, December 2012.